Auxiliary Part of Ligand Mediated Unique Coordination Chemistry of Copper (II). Issue 3 (24th March 2016) - Majumder, Ishani; Chakraborty, Prateeti; Adhikary, Jaydeep; Kara , Hulya; Zangrando, Ennio; Bauza, Antonio; Frontera, Antonio; Das, Debasis
Abstract: Six N, N, O‐donor Schiff‐base ligands, HL1‐HL6, [HL1/HL2/HL3={2‐(2‐piperazin‐1‐yl)ethylimino)methyl)‐4‐(Cl/H/Me)‐phenol}; HL4/HL5/HL6={2‐(2‐morpholine/piperidine/ pyrrolidine −1‐yl)ethylimino)methyl)‐4‐chlorophenol}, have been designed by combining 5‐R‐2‐hydroxy‐benzaldehyde, (R=Cl/H/Me) and N‐(2‐aminoethyl)‐Y, (Y=piperazin/morpholine/ piperidine/pyrrolidine) with the view to explore the role of R and X (part of Y excluding coordinating N) on the coordination chemistry of Cu(II) in presence of bromide as counter anion. HL1‐HL6 formed in situ on reaction with Cu(II)Br2 produce complexes1–6, respectively. Complex1, [ Cu(II)2 Cu(I)2 (L1)(MeOH)2 Br7.30 ], is a mixed valence Cu(I)‐Cu(II) species having phenyl ring brominated at ortho position with 0.65 occupancy. Complexes2–4 are mononuclear species with general formula [Cu{L2/L3/L4)}Br2 ]. Complexes [Cu3 (L5)Br4 ] (5) and [Cu3 (L6)Br4 ] (6) are trinuclear species having similar structure but exhibit different magnetic property, 5 is ferro‐ ( J = +16.64 cm −1 ) and6 is antiferromegnetic ( J =–11.76 cm −1 ). The influence of R and X on bromonation, magnetic property and nuclearity issues have been rationalized by DFT calculations. Abstract : The influence of the auxiliary part i. e., the atom or group of atoms which is present in the ligand periphery but apparently has no effect on ligating backbone or on the chelating property of the ligand and is not directly linked with the coordination environment of the metal ion of N, N, O‐donor Schiff‐base ligands, {2‐(2‐Y‐1‐yl)ethylimino)methyl)‐4‐R‐phenol} (R=Cl/H/Me; Y=piperazin/morpholine/piperidine/ pyrrolidine) become instrumental in yielding bromination in phenolic ring, generating structural diversity and in producing ferro‐ and antiferromagnetic interactions amongst the copper(II) centers.